Understanding humanitarian diplomacy : principles and practice - Kavak, Hafize Zehra (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"This book introduces readers to the development, principles, and philosophy of humanitarian diplomacy, before demonstrating how it works in practice, using a range of case studies from humanitarian work in the field. Humanitarian diplomacy seeks to create avenues to persuade decision makers and opinion leaders to act, at all times, in the interests of vulnerable people and with full respect for fundamental humanitarian principles. This book considers the historical evolution of humanitarian diplomacy, its theoretical underpinnings, its relationship with classic diplomacy, international law, and the greater ecosystem in which it exists, and the characteristics and attitudes essential for humanitarian diplomats. The book also draws on a range of first-hand experiences to showcase humanitarian diplomacy's success in solving humanitarian issues. In doing so, it draws attention to the challenges faced by humanitarian workers and serves as an invaluable roadmap for aspiring humanitarians. Bringing an excellent balance of theory and practice, this book will be a perfect guide for students and practitioners looking to understand the historical, philosophical, legal, and practical foundations of humanitarian diplomacy"--
Keywords: Humanitarian intervention -- Philosophy; Diplomacy; Humanitarian intervention -- Case studies